The impact of COVID-19 on medical tourists: A content analysis - Zeng Tian (2022)
COVID-19 is considered to be the most influential pandemic, which has caused panic all over the world. As a result of epidemic prevention and control measures, the state of life and the development of the industry have changed dramatically. During the pandemic, the medical tourism industry was greatly affected. As a result, there is a lack of research related to the behavior of medical travelers during the pandemic. This study aims to gain insight into the consumers who still choose medical tourism from the beginning of the pandemic outbreak and to examine the differences by age. In this study, the participants are 70 medical tourists from March 2020 to the present, and to ensure the accuracy of the study, the direction of the study was focused on dental treatment. Medical tourists' reviews are collected on the Treatment abroad website and then analyzed for participants and text content using Leximancer. The results of the research indicated a slight change in the percentage of medical tourists by age group, with an increase in the percentage of middle-aged and older individuals. Meanwhile, due to the special period of COVID-19, medical tourists are more concerned about the details and quality of services. And compared to younger medical travelers, middle-aged and older people are more concerned about the level of medical technology. Moreover, in the post-COVID-19 period, medical tourism industry personnel must understand the characteristics and trends of potential consumers and develop appropriate strategies to deal with the new situation.